Classroom management for elementary teachers - Evertson, Carolyn M. (Pearson, 2009)
Evertson (Peabody College, Vanderbilt U.) and Emmer (U. of Texas at Austin) provide a handbook on establishing and maintaining a comprehensive classroom management plan. It covers classroom arrangement; rules and procedures; managing behavior, student work, instruction, and cooperative learning groups; communication skills; problem behaviors; and special groups like students with special needs and lower-achieving students. This edition has updated questions, activities, and references; expanded coverage of parental involvement, including home-school communication and example letters; more on bullying, power struggles, defiance, and school violence; and updated coverage of autism spectrum disorders.